The Commonwealth brand global voice, local action - Te Velde, Victoria (Ashgate Pub., 2011)
This book examines Commonwealth identity through the lens of its membership criteria, its recent enlargement and its constant reincarnation. In so doing it exposes various shortcomings in current thinking about international relations and the Commonwealth.